(untitled) (American Journal of Pedagogical and Educational Research, 2025)
Artificial Intelligence (AI) has significantly reshaped the way English is taught and learned. This article explores the various ways AI influences English language learning, such as adaptive learning platforms, language translation tools, and virtual tutors. By analyzing the benefits and challenges of AI integration, this study aims to provide a comprehensive understanding of its role in language education. The findings indicate that AI offers personalized and efficient learning experiences, but also raises concerns regarding dependency and accessibility.